Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Di CV. Sriwijaya Propertirindo Jaya - R.A Rodia Fitri Indriani (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to describe and analyze the effect of the work environment on employee performance. The type of research used is explanatory research. The number of samples in this study were 29 employees of CV Sriwijaya Properterindo Jaya. This study uses an correlation research method using a quantitative approach. The study explains the relationship between variables through hypothesis testing that has been formulated previously. Through this hypothesis test, it is expected to be able to explain the influence of the work environment on employee performance. Data collection techniques using the stages of observation, giving questionnaires to research subjects. Analysis of the data used is descriptive analysis and simple regression analysis. The results of this study indicate that based on descriptive analysis shows that the majority of respondents agree that the existing work environment in the company is good so that employee performance increases. The hypothesis of this study states that the work environment has a positive and significant effect on the performance of employees of CV Sriwijaya Properterindo Jaya. The results showed the value of = 0.570. The value of t count (5.829) > t table (2.01) with a significance value (0.000) less than alpha 0.05, then the hypothesis is accepted. This means that the work environment has a positive and significant effect on the performance of CV Sriwijaya Properterindo Jaya employees.